Building Regional Language Awareness Through Personal and Social Communication As An Acculturation Efforts - A. Dian Fitriana Eka Putri; Muhammad Sahid (State Islamic Institute of Bone, Indonesia, 2020)
AbstractAdjustment is one step taken by someone to be able to survive in a new place. An immigrant (nomads) make adjustments when in a new culture, and that is known as acculturation. Acculturation efforts are certainly supported by the existence of communication between immigrant and indigenous communities, both personal and social communication. This study aims to determine the effectiveness of Persona Communication and Social Communication Against Language Culture Awareness. This research uses descriptive qualitative research methods. The sampling technique is a purposive sampling technique. Data collection is done by Interview, Observation, and Literature Study. The results of this study indicate the effectiveness of communication both personal and social in nature which is quite a big influence and is carried out by overseas students from South Sulawesi to the local community in the city of Bandung. The communication carried out both persona and social has an impact on the acculturation that they do in their overseas locations. Key Words : Communication; Awareness; Regional Language.